New lacewings (Insecta, Neuroptera, Osmylidae, Nymphidae) from the Lower Cretaceous Burmese amber and Crato Formation in Brazil. (April 2016) - Myskowiak, Justine; Huang, Diying; Azar, Dany; Cai, Chenyang; Garrouste, Romain; Nel, André
Abstract: One new osmylid genus and species, Burmaleon magnificus, and one new nymphid genus and species Rafaelnymphes cratoensis are described, respectively based on inclusions in the Cretaceous Burmese amber and on a compression fossil from the Crato Formation in Brazil. The nymphid Araripenymphes seldeni, from the Crato Formation, is redescribed on the basis of a new specimen, showing possible sexual dimorphism in wing coloration, a feature extremely rare among the Neuroptera. In a recently published phylogenetic analysis of the family, the attribution to the fossil taxa (versus rejection) of the larval characters proper to the modern nymphids, has a crucial impact on the resolution of the phylogeny. The compression fossils currently attributed to the Nymphidae should be revised because their wing venation alone is not really sufficient for an accurate family attribution to Nymphidae rather than to another family of Neuroptera (viz. Osmylidae).